Automatic and Efficient Allocation for Examination Seats using Android Application (International journal of innovative technology and exploring engineering, 2019)
This paper is resolved to streamline the errand of manual seating game plan of understudies in an examination lobby. The main goal is to develop an android app for automatic examination seating arrangement in addition to reducing the manual work of staff. A PDF containing student exam number with subject code and subject name will be sent by the university and will be received by the admin staff which will be converted into suitable format. Then an algorithm will be used to involuntarily allocate the students to the suitable block according to their strength. Then the staff will be randomly allocated to particular block. Alternating staff allocation will be done according to department. The students and the staff will receive a message regarding the block where they have been assigned. In this paper we can further add features to improve the flexibility.